ANTIOXIDANT ACTIVITY OF BINJAI LEAVES(Mangifera caesia) ETHANOL EXTRACTS (Research report) - Anita Diana Putri; Irham Taufiqurrahman; Nurdiana Dewi (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Binjai is one of Mangifera species which commonly found in South Kalimantan. Binjai leaves are known to contain flavonoids compounds, that have an effect as antioxidant that can accelerate wound healing process after tooth extraction. This study was conducted to examine the variation of  solvent concentration towards antioxidant activity of Binjai’s leaves extract using maceration method. Antioxidant activity is tested with DPPH (2,2-diphenyl-1-picrylhydrazyl) and examined using Spectrophotometer UV-Vis. Purpose: This study aims to determine solvent concentration which exxpres optimal antioxidant activity of Binjai leaves extract. Methods: This study is a true experimental with post-test only control group design. The sampling technique of Binjai leaves was determined by simple random sampling and 7 samples was opted for each treatment. Results: The study revealed that 96% ethanol extract of Binjai leaves obtained IC50 (Inhibitory Concentration) as much of 16.14 ppm (very active), 70% ethanol extract of the Binjai leaves obtained 37.94 ppm (very active), and 50% ethanol extract of Binjai leaves obtained 58.07 ppm (active). Data analysis was conducted using One Way ANOVA parametric test and LSD post hoc test which demonstrated a significant difference among 96%, 70% and 50% of ethanol  extracts of Binjai leaves with p = 0.000 (p <0.05). Conclusion: Binjai leaves extracted using 96% ethanol solvent possesses higher level of antioxidant activiy compared to 70% and 50% ethanol concentration.